Brewing prosperity: An analysis of living income gaps among coffee smallholders in central Kenya - Boukaka, Sedi Anne; Benfica, Rui (International Food Policy Research Institute, 2025)
This study investigates the living income gap among coffee smallholders in central Kenya. It uses detailed survey data collected from coffee farmers organized in cooperatives and from coffee farm workers in Nyeri and Murang’a counties. Our analysis finds that coffee smallholders earn an average of only 109 KSh per day, just 35 percent of the 312 KSh living income benchmark, with the gap being particularly severe in Murang’a and among those with smaller landholdings. Sensitivity analyses show that enhancing prices paid to farmers and improving yields can partially reduce the income shortfall. For instance, doubling both parameters, especially when coupled with a 50 percent increase in farmers’ non-coffee income, lowers the incidence of households below the benchmark from more than 90 percent to about 67 percent. Yet, even under these relatively optimal conditions, the persistence of a significant gap underscores deep structural constraints in the local economy. Policy recommendations therefore call for a multidimensional approach that improves production efficiency, improves and stabilizes prices, promotes income diversification, and strengthens institutional support.